The effect of ordinary portland cement substitution on the thermal stability of geopolymer concrete - Zhang, Hongen; Li, L.; Long, T.; Sarker, Prabir; Shi, X.; Cai, G.; Wang, Q. (2019)
© 2019 by the authors. The influence of using cement on the residual properties of fly ash geopolymer concrete (FAGC) after exposure to high temperature of up to 800 °C was studied in terms of mass loss, residual compressive strength and microstructure. The mass loss was found to increase with the increase of exposure temperature, which is attributed to vaporization of water and dehydroxylation of sodium aluminosilicate hydrate (N-A-S-H) gels. The dehydroxylation of calcium silicate hydrate (C-S-H) gels and the disintegration of portlandite were responsible for higher mass loss ratio of FAGCs containing cement. The results showed that cement could increase compressive strength of FAGCs up to 200 °C, after which a significant reduction in residual strength was observed. It was found that FAGCs without cement yielded higher residual strength than the original strength after heating up to 600 °C. The observed increase of compressive strength up to 200 °C was attributed to the secondary geopolymerization which was evidenced in the scanning electronic microscopy (SEM) images.